Sustainable Treatment of Emerging Organic Pollutants (Eops), Endocrine Disruption Chemicals (Edcs) from Water & Waste Water and Role of AIU Online Based Distance Learning Education System to Achieve UNESCO 2030 Goals Towards Sustainable Development - Islam, Mohammad Shahidul; Sangaran, Sumathi (European Journal of Applied Sciences, 2022)
Complete mineralization of EOPs including EDCs is one of the challenges towards sustainable management practice of water and waste water treatment systems. Ozone gas has been identified as an effective oxidant against mineralization of these chemicals. Optimization of factors affecting ozonolysis is vital towards mineralization of EDCs. For this kinetic study of ozonolysis degradation of EDCs in two phase gas-liquid systems is performed in a semi[1]batch reactor observing Total Organic Carbon (TOC) degradation for process optimization. Concentration of initial substances, temperature of the system and sparger/bubble size have significant effect on ozonolysis of EDCs. They are considered as dominant factors to be optimized. Temperature dependency of specific kinetic constants of model EDCs, i.e., Diclofenac Sodium (DFS) has been determined by taking into account the specific volume change due to ozone dosing. From this the activation energy for DFS has been determined to be 26.4 KJ/mol using the well known Arrhenius rate equation. These information together with sparger effect have been incorporated to find optimum values of the process variables for ozonolysis of EDCs in water and wastewater without using any catalyst so that the simplicity of the ozonolysis process can be preserved. Results obtained in work will help water treatment industries to develop sustainable ozonolysis technique to treat EDCs at optimized process condition.